Evolution of CsPbBr3 nanocrystals upon post-synthesis annealing under an inert atmosphere. Issue 39 (26th September 2016) - Palazon, F.; Di Stasio, F.; Lauciello, S.; Krahne, R.; Prato, M.; Manna, L.
Abstract : Annealing a film of CsPbBr3 nanocrystals (NCs) leads to the removal of surface ligands and ripening of the NCs below 200 °C. Abstract : Annealing a film of CsPbBr3 nanocrystals (NCs) leads to the removal of surface ligands and ripening of the NCs below 200 °C. This results in a reduced photoluminescence quantum yield due to the formation of trap states while on the other hand the conductive properties of the films are stabilized, with a significantly stronger photocurrent after annealing.